2022
DOI: 10.5539/elt.v15n2p31
|View full text |Cite
|
Sign up to set email alerts
|

Public Speaking and Online Peer Feedback in a Blended Learning EFL Course Environment: Students’ Perceptions

Abstract: This paper reports on a blended learning approach for public speaking in an English as a foreign language (EFL) context. The researcher implemented the course design through reduced weekly face-to-face class sessions and online student interaction using a speech video-based blog. Using a survey conducted at the end of the semester, multiple comments provided for online peer feedback, structured outlines submitted to Turnitin, and instructor’s weekly observation of the students’ presence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…In the context of language learning, peer feedback can improve learners’ L2 language skills and public speaking presentation skills (El Mortaji, 2022 ; Patri, 2002 ). Rodríguez-González and Castañeda ( 2016 ) found that peer feedback can improve L2 speaking skills and feelings of self-confidence and self-efficacy.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…In the context of language learning, peer feedback can improve learners’ L2 language skills and public speaking presentation skills (El Mortaji, 2022 ; Patri, 2002 ). Rodríguez-González and Castañeda ( 2016 ) found that peer feedback can improve L2 speaking skills and feelings of self-confidence and self-efficacy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rodríguez-González and Castañeda (2016) found that peer feedback can improve L2 speaking skills and feelings of self-confidence and self-efficacy. Peer feedback practice can improve learners' ability to detect language errors (Fujii et al, 2016), and PCF has been found to be a "feasible option for helping learners to attend to form in effective ways during peer interaction" (Sato & Lyster, 2012, p. 618). Conversely, Adams et al (2011) found that peer feedback had a negative effect on L2 learning.…”
Section: Efficacy Of Peer Feedbackmentioning
confidence: 99%
See 2 more Smart Citations
“…Ключові слова: ораторська майстерність, риторична підготовка, інформаційно-комунікаційні технології, онлайн-платформи, дистанційне і змішане навчання. [3], проєктний підхід у риториці -В. Нищита [9], питання розвитку публічних навичок з використання платформи Microsoft Teams досліджують J. Gotlib, M. Jaworski [10], проблему публічних виступів та зворотного зв'язку онлайн під час змішаного навчання описує L. Mortaji [11], типологію електронних ресурсів у формуванні риторичної культури фахівця описали Д. Будянський, М. Друшляк, О. Семеніхіна, І. Харченко, В. Горбачук, О. Чашечникова [1], які серед електронних ресурсів…”
Section: статтю присвячено питанню формування та розвитку ораторської...unclassified